2023
DOI: 10.3390/fishes8070364
|View full text |Cite
|
Sign up to set email alerts
|

Captive Reproductive Behavior, Spawning, and Early Development of White-Barred Goby Amblygobius phalaena (Valenciennes, 1837) and Examined Larval Survival and Viability at Different Water Temperatures and Salinities

Abstract: White-barred goby Amblygobius phalaena is a highly valued marine ornamental fish, but its captive reproduction and early life history are poorly understood. In this study, the captive reproductive behavior, early development, and optimal temperature and salinity for the larval survival and viability of A. phalaena were investigated for the first time. Spawning occurred between 11:00 and 13:00, with the breeding pairs naturally spawning 24 times from 1 June 2021 to 30 June 2022. The fecundity ranged from 11,022… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Experiment 1 revealed that rotifers B. rotundiformis and copepod A. royi nauplii were not suitable as initial live prey for White-barred Goby larvae, suggesting that the larval White-barred Goby in the previous study (Chiu et al 2023) relied on ciliates Euplotes sp. to pass through the first feeding stage.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Experiment 1 revealed that rotifers B. rotundiformis and copepod A. royi nauplii were not suitable as initial live prey for White-barred Goby larvae, suggesting that the larval White-barred Goby in the previous study (Chiu et al 2023) relied on ciliates Euplotes sp. to pass through the first feeding stage.…”
Section: Discussionmentioning
confidence: 85%
“…In this study, four types of live feed organisms were used: ciliates Euplotes sp., trochophores of the Portuguese oyster Crassostrea angulata, rotifers B. rotundiformis, and copepod A. royi nauplii (Table 2). All four live feed organisms were smaller than the mouth gape height of White-barred Goby during first feeding, which ranges from 238.45 to 298.21 μm (Chiu et al 2023).…”
Section: Live Feed Organism Culture and Preparationmentioning
confidence: 80%
See 2 more Smart Citations
“…To effectively establish aquaculture practices for a speci c species, it is necessary to have a comprehensive understanding of various aspects. This includes knowledge about the species' captive spawning (Mylonas et al 2010), optimal water quality conditions for the survival of fertilized eggs and larvae (Chiu and Leu 2021; Leu et al 2022;Chiu et al 2023), as well as the appropriate live feed organisms (Conceição et al 2010;Pan et al 2022). Within the Scomberomorus genus, the Japanese Spanish mackerel (S. niphonius) has relatively comprehensive information available for arti cial cultivation (Fukunaga et al 1982;Tanaka 2001, 2005;Sugino et al 2005).…”
Section: Introductionmentioning
confidence: 99%